2008
DOI: 10.1177/1087057108328016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Variability and Sensitivity between Nuclear Translocation and Luciferase Reporter Gene Assays

Abstract: High-content screening (HCS), a technology based on subcellular imaging by automated microscopy and sophisticated image analysis, has emerged as an important platform in small-molecule screening for early drug discovery. To validate a subcellular imaging assay for primary screening campaigns, an HCS assay was compared with a non-image-based readout in terms of variability and sensitivity. A study was performed monitoring the accumulation of the forkhead transcription factor of the O subfamily (FOXO3a) coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This result is consistent with previous work showing the poor correlation between FOXO1 localization and transactivation activity. 18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is consistent with previous work showing the poor correlation between FOXO1 localization and transactivation activity. 18 …”
Section: Resultsmentioning
confidence: 99%
“…18 Unterreiner et al showed a poor correlation between hits from image-based screening of FOXO3 activators and those from reporter-based screening. 18 Kau et al identified inhibitors of FOXO1 nuclear export, but whether these inhibitors affect the transcriptional activity of FOXO1 was not reported. 19 Our data are consistent with the interpretation that nuclear translocation is only one mechanism of FOXO1 regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both assays were equally reproducible, but the HCS assay had a better statistical quality. The HCS assay was more sensitive than the RGA although it was not able to identify additional chemical scaffolds as hits (Unterreiner et al, 2009). However, this study represents only one HCS assay and one RGA, and the picture might change when comparing more assays.…”
Section: What Are the Benefits Of High-content Screeningmentioning
confidence: 99%